2016
DOI: 10.11622/smedj.2016050
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management of acute airway obstruction

Abstract: The acutely obstructed airway is a medical emergency that can potentially result in serious morbidity and mortality. Apart from the latest advancements in anaesthetic techniques, equipment and drugs, publications relevant to our topic, including the United Kingdom's 4th National Audit Project on major airway complications in 2011 and the updated American Society of Anesthesiologists' difficult airway algorithm of 2013, have recently been published. The former contained many reports of adverse events associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…During planning for routine anaesthesia, the ASA has suggested that four decisions need to be made:15 awake or asleep intubation, spontaneous ventilation (SV) or ablation of SV, non-invasive or invasive airway techniques and direct or indirect laryngoscopy 19. During emergency airway management, these decisions need to be made in the context of the location of the patient, location of equipment required to perform each technique and safety of transporting the patient to the equipment or vice-versa.…”
Section: Discussionmentioning
confidence: 99%
“…During planning for routine anaesthesia, the ASA has suggested that four decisions need to be made:15 awake or asleep intubation, spontaneous ventilation (SV) or ablation of SV, non-invasive or invasive airway techniques and direct or indirect laryngoscopy 19. During emergency airway management, these decisions need to be made in the context of the location of the patient, location of equipment required to perform each technique and safety of transporting the patient to the equipment or vice-versa.…”
Section: Discussionmentioning
confidence: 99%
“…(35,36) However, in severe cases, awake FOI is contraindicated (see Page 116, 'Acute airway obstruction'). (37) The addition of sedation allows for a more cooperative patient. Options include small intravenous boluses of opioids or benzodiazepines, and intravenous infusions of sedatives using total intravenous anaesthesia or target-controlled infusions.…”
Section: Awake Intubation With Spontaneous Ventilationmentioning
confidence: 99%
“…In cases of predicted or known difficult laryngoscopy, the FOB is ideal for navigating the airway and bypassing oropharyngeal lesions due to the insertion cord's thin diameter and high manoeuvrability. However, in severe acute airway obstruction, its use is contraindicated for several reasons: (37) the patient is not calm or cooperative enough; airway topicalisation and/or sedation may cause loss of airway, including laryngospasm; (32)(33)(34) navigation of the FOB is difficult; bleeding or complete obstruction may occur; (28,83) and railroading of the tracheal tube may fail. (28,83) As such, the NAP4 cautioned that "the role of awake FOI is debatable" in these cases.…”
Section: Acute Airway Obstructionmentioning
confidence: 99%
“…Murphy's eye on the connecting endotracheal tube was trimmed-off to ensure a wider and straighter tube at the join [5]. As a precaution, the extracorporeal membrane oxygenation (ECMO) team was on stand-by during induction of anesthesia.…”
Section: Case Reportmentioning
confidence: 99%